How did a Lutheran astronomer get converted into a catholic authority? The Jesuits and their reception of Tycho Brahe in Portugal - Carolino, L. M. (Bristish Journal for the History of Science, 2024)
This article explores the complex process of integrating Tycho Brahe's theories into the Jesuit intellectual framework through focusing on the international community of professors who taught mathematics at the College of Saint Anthony (Colégio de Santo Antão), Lisbon, during the first half of the seventeenth century. Historians have conceived the reception of the Tychonic system as a straightforward process motivated by the developments of early modern astronomy. Nevertheless, this paper argues that the cultural politics of the Counter-Reformation Church curbed the reception of Tycho Brahe within the Jesuit milieu. Despite supporting the Tychonic geo-heliocentric system, which they explicitly conceived of as a ‘compromise’ between the ancient Ptolemy and the modern Copernicus, and making recourse to some of the cosmological ideas produced in Tycho's Protestant milieu, the Jesuits strove to confine the authority of the Lutheran astronomer to the domain of mathematics. Philosophy was expected to remain the realm of Catholic orthodoxy. Thus, while Tycho Brahe entered the pantheon of ‘Jesuit’ authorities, he nonetheless was not granted the absolute status of intellectual authority. This case demonstrates how the impact of confessionalization reached well beyond the formal processes of science censorship.